MUTUAL AID IN SOCIAL REINTEGRATION OF FORMER TERRORIST PRISONER IN INDONESIA - SAIFUDIN ASRORI; AHMAD SYAUQI (Social Welfare Study Program, 2020)
Abstract. The involvement of former terrorist prisoners in social and economic empowerment efforts, especially members or ex-convicts who disengage the terrorist groups is an interesting and unique phenomenon. This article aims to explore the empowerment of ex-terrorist convicted on de-radicalization and social reintegration disengaging terrorist back into society. Through interviews of several activists ex-Jihadist and observation of empowerment programs, this article conclude that the former terrorist prisoner’s engagement in the empowerment initiatives as an alternate of government deradicalization programs of former terrorist prisoner. This group became the ‘new community’ for ex-extremists to express various views and believe without concealment. The presence of this group is a potential asset in promoting narratives against radicalism and terrorism in Indonesia. Abstraks. Pelibatan mantan narapidana teroris dalam upaya pemberdayaan sosial dan ekonomi, khususnya anggota atau mantan narapidana yang memisahkan diri dari kelompok teroris merupakan fenomena yang menarik dan unik. Artikel ini bertujuan mengeksplorasi pemberdayaan eks narapidana teroris melalui deradikalisasi dan reintegrasi sosial untuk kembali ke masyarakat. Melalui wawancara beberapa mantan aktivis jihadis dan observasi program pemberdayaan, artikel ini berkesimpulan bahwa pelibatan mantan narapidana teroris di dalam upaya pemberdayaan sebagai program deradikalisasi alternatif dari pemerintah terhadap para eks napi teroris. Mereka bisa menjadi sebuah komunitas baru untuk para eks-ekstremis dalam mengungkapkan pandang dan keyakinan mereka secara terang-terangan. Kehadiran kelompok (mereka) ini menjadi aset penting dalam upaya mendorong narasi terhadap radikalisme dan terorisme di Indonesia.